Analisis Pendapatan Usaha Tani Salak Bali (Sallacca edulis Reinw) di Desa Batu Nindan Kecamatan Basarang - Neni Widaningsih; Muhammad Ilmi Hidayat; Muhamad Musair (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2013)
This study aims to determine the technical know bali farming barking and barking analyzing farm income bali ( Sallacca edulis Reinw) in the village of Batu Nindan Basarang district . Time research was conducted from 4th June to 30th November 2012. The types of data collected in this study included primary data and secondary data. This research method using a survey method . Sampling was done using purposive sampling technique, 30 of 86 people barking bali farmer in the village of Batu Nindan . The variables observed in this study is technical farm income analysis barking and barking bali in the village of Batu Nindan. Research results indicate that farming Technical bali barking in the village of Batu Nindan done extensively . The average total cost of Farm bali barking amounted Rp.3.989.006 with average revenues of Rp.3.822.567 and the average income of Rp.3.400.324 . Bali barking farming held in the village of Batu Nindan inefficient or not feasible to be developed with an average value of RCR Rp.0 , 96 , - ( < 1 )